The Effect Carrot (Daucus carota L) Addition to Ledok Characteristics - Hutabarat, Fransen Kennedy; Yusa, Ni Made; Wiadnyani, A.A.I Sri (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2017)
This research was conducted to determine effect of carrot on the characteristics ledok and the proper concentration of a carrot right to produce ledok with the best characteristics. The research method was use a randomized block design analysis with 5 treatment of the concentration carrot additions of 0%, 10%, 20%, 30% and 40%. Each treatment was repeated three times to obtain 15 experimental units. Data were analyzed by analysis of variance followed by Duncan test. The results showed that the addition of carrots significant effect on water content, ash content, fat content, protein content, carbohydrate content, betacarotene levels and sensory attributes tests ledok. Based on nutrient content and sensory attributes of ledok, best amount is the addition of carrots 40% with the following characteristics water content 73,77%, ash content 0.96%, protein content 4,06%, carbohydrate content 16,34%, fat content 4,83%, betacarotene 379,85 ppm, colour 6,53, aroma 3,73, taste 5,73, and overall acceptance of 5,20.